Arbuscular mycorrhizal fungi influence decomposition and the associated soil microbial community under different soil phosphorus availability. (May 2018) - Xu, Jing; Liu, Shijun; Song, Shurui; Guo, Hanling; Tang, Jianjun; Yong, Jean W.H.; Ma, Yuandan; Chen, Xin
Abstract: Despite the general appreciation that arbuscular mycorrhizal fungi (AMF) can influence decomposition of organic materials, the underlying mechanisms remain unclear. Here we investigated whether AMF influence decomposition and change the associated soil bacterial and fungal communities through nutrient acquisition and whether this effect is altered by the level of soil phosphorus (P). We conducted a pot experiment using Medicago truncatula as host plant without or with AMF (a mixture of six species) and with two levels of soil P (4 and 24 mg kg −1 ). Hyphal-ingrowth mesh bags (which excluded roots but not hyphae or other microbes) were used to measure the effect of AMF hyphae on decomposition. Maize leaves dual-labeled with 15 N: 13 C stable isotopes were used as the organic substrate. Bacterial and fungal communities were accessed via sequencing of partial 16S rRNA and ITS genes. The results showed the 15 N and 13 C content of the organic matter remaining in the mesh bags under low soil P availability were significantly lower in the treatment with AMF than without AMF. Under high soil P availability, however, no significant difference of 15 N content remaining was found between AMF and non-AMF treatments, while 13 C content remaining was higher in AMF than in non-AMF treatment. Levels of mycorrhizal colonization and 15 N transport from organic matter to the host by AMF hyphae were higher at low P availability than at high P availability, suggesting that the host can acquire more nutrients through the AM from organic matter when soil P availability was low. The composition of bacterial and fungal communities were altered by AMF at both soil P levels. For bacterial community, the richness and diversity were higher with low P availability, especially for the phyla Saccharibacteria and Nitrospirae. For fungal community, AMF increased the richness but not the diversity under low P availability. Together, we show that AMF acquire nutrients from organic matter for host, influence decomposition and alter the bacterial and fungal communities, and that these effects were modulated by the soil P availability. Highlights: Arbuscular mycorrhizal fungi (AMF) affected organic matter decomposition in soil. The effects of AMF on decomposition depended on soil phosphorous (P) levels. The bacterial and fungal communities changed in the AMF hyphosphere. Enhanced decomposition by AMF improved host plant nutrition under low soil P.